The role of PAM in pancreatic beta cell dysfunction and diabetes - Sengupta, S (2019)
Genome wide association studies (GWAS) have been critical to the identification of >400 signals at around 200 loci involved in Type 2 Diabetes (T2D) risk. However, the functional interrogation at these loci has been slow. Coding alleles in PAM, D563G (minor allele frequency, MAF=4.98%) and S539W (MAF=0.65%), were identified in association with increased Type 2 diabetes (T2D) risk and reduced insulinogenic index. These were recently shown to mediate risk through alterations to PAM amidating activity and expression in the β cell. Peptidylglycine -amidating monooxygenase (PAM) was also recently shown to function in mediating insulin secretion and content. The work in this thesis has explored the role for PAM in pancreatic beta (β) cells and the cellular mechanisms by which its dysfunction alters diabetes risk across a range of diabetes phenotypes ranging from classical T2D through early onset diabetes pathogenesis. First, I characterised the role for PAM in human pancreatic β cells using an authentic cell model, EndoC-βH1 cells. Examination of endogenous PAM expression identified the predominant isoform to be membrane-integral, which localised to insulin-containing secretory granules and was post-translationally cleaved to generate 2 further isoforms. Gene silencing and PAM catalytic inhibition studies identified that auxiliary proteins present in the secretory granule, such as chromogranin A, are amidated by PAM and that this may impact their stability and localisation. In addition, reduced intracellular insulin content mediated through impaired PAM activity was shown to be mediated through reduced INS gene expression. Next, I determined the impact of a rare coding allele (p.R36S) on PAM and β cell function, identified in a proband with early onset diabetes mellitus. I compared the T2D-associated low frequency allele, S539W, which results in a loss of PAM function, with this novel allele to explore how these alleles might differ in their effect on β cells. Comparison of the cellular dysfunction between these two alleles identified that R36S-PAM caused β cell loss in contrast to the T2D-risk allele S539W which impaired insulin secretion. Finally, I established a strategy to characterise rare variants identified in a gene-level signal for T2D risk in PAM. A comprehensive functional characterisation is needed to fully elucidate the relationship between altered PAM function and T2D risk. A pilot study of 5 of the 35 variants underlying the association identified a further PAM allele which caused reduced protein expression. In summary, my work has uncovered the complex biology pertaining to PAM function in β cells and distinct mechanisms by which dysfunction may lead to diabetes of differing clinical severities. A more comprehensive understanding of these mechanisms may potentially inform diagnosis and drug development for diabetes along the spectrum of clinical severity.